2016
DOI: 10.1039/c5cc10037b
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of P4 in the coordination sphere of coinage metal cations

Abstract: Selective functionalization of white phosphorus is achieved by addition of ArLi to unique cationic coinage metal η2–P4 complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Lammertsma and co‐workers recently reported that the N ‐heterocyclic carbene (NHC) gold complex 90 readily reacts with aryl lithium compounds at low temperatures (Scheme 15 c). [52] The controlled P−C bond formation and concomitant cleavage of one P−P bond gives rise to the proposed intermediate butterfly species 91 . Immediate addition of a second [(NHC)Au] fragment, derived through formal loss of P 4 from a second equivalent of 90 , affords the cationic complex 92 in high yield.…”
Section: Transition‐metal‐mediated Functionalization Of White Phosphorusmentioning
confidence: 99%
“…Lammertsma and co‐workers recently reported that the N ‐heterocyclic carbene (NHC) gold complex 90 readily reacts with aryl lithium compounds at low temperatures (Scheme 15 c). [52] The controlled P−C bond formation and concomitant cleavage of one P−P bond gives rise to the proposed intermediate butterfly species 91 . Immediate addition of a second [(NHC)Au] fragment, derived through formal loss of P 4 from a second equivalent of 90 , affords the cationic complex 92 in high yield.…”
Section: Transition‐metal‐mediated Functionalization Of White Phosphorusmentioning
confidence: 99%
“…The isolation and versatility of the stabilized [RP 4 ] − anion 4 marks a significant step toward the controlled functionalization of P 4 with organolithium reagents. Interestingly, related RP 4 derivatives can also be generated from P 4 in the coordination sphere of a gold(I) cation, even with unencumbered MesLi, which is otherwise precluded due to rapid quenching with boron Lewis acids to Li[MesBAr 3 ]. Exemplary is the reaction of ArylLi with the η 2 ‐P 4 ‐coordinated cationic (NHC)Au I complex 12 (Scheme ; Aryl=Mes or Dmp, NHC= N ‐heterocyclic carbene) that afforded selectively the neutral bicyclic tetraphosphanes 13 , which coordinates to an additional gold cation complex with displacement of a P 4 molecule to give bimetallic 14 .…”
Section: Functionalization Of P4 Using Main Group Metal Organylsmentioning
confidence: 99%
“…On the contrary, concerning P 4 and polyphosphorus (P n ) complexes, fewer Au coordination compounds are known. Reactions of Au­(I)Cl species with a chloride abstractor (e.g., GaCl 3 or LiTEF) and P 4 led to discrete coordination compounds . Interestingly, Forfar et al carried out similar reactions with Cu and Ag salts as well .…”
Section: Introductionmentioning
confidence: 99%